COMPARING THE VALUE RELEVANCE OF SELECTED ACCOUNTING INFORMATION IN CONSOLIDATED AND SEPARATE FINANCIAL STATEMENTS: THE CASE OF NIGERIAN LISTED FINANCIAL SERVICE FIRMS (Journal of Economics and Sustainability, 2021)
In a company with a group structure, financial information is presented in two folds via consolidated and separate financial statements. The reporting of the similarly classified elements of financial statements arranged side by side in two columns carrying two different figures may be puzzling. Consequently, investors and other financial information users having two different figures available to them need to be guided as to which set(s) of information they need to make predictions and decisions. This study provides evidence about the comparative value relevance of accounting information for consolidated and separate financial statement of listed financial service firms in Nigeria. The study population is the entire listed financial services firms throughout the period of 2014-2018.